Uncovering Gender and Age Neutrality in CT Values for E and RdRp Gene Amplification in SARS-CoV-2 - Ibrahim A. Naqid; Masood Ahmed Hameed; Nawfal R. Hussein; Shivan Hassan Yousif (QAASPA Publisher, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic poses a danger to public health across the world. Specific and sensitive testing is vital to tracking and containing the infected individuals. This study examines the characteristics of 705 patients based on gender and age groups, with a focus on their CT (Cycle Threshold) values associated with E- and RdRp gene amplification. Among the patient cohort, 58.87% were male, while 41.13% were female. Notably, all males and females tested positive for the E gene, achieving a 100% detection rate, whereas the RdRp gene exhibited a slightly lower positive rate of 93.4% in males and 89.6% in females. Statistical analysis through the chi-square test revealed no significant disparities between target genes and gender. Additionally, a one-way ANOVA test demonstrated no significant distinctions between target genes and age groups. This study's findings suggest that gender and age do not significantly influence CT values for E and RdRp gene amplification, and there is no preferred gene for detection, providing valuable insights into the molecular characteristics of the studied cohort.